Employees peception towards code of ethics in banking sectors at Kuching / Unyang Laeng Jau & Yunizar Yusop - Jau, Unyang Laeng; Yusop, Yunizar (2013)
In this chapter is going to discuss a review of the literature on employees’ perception towards code of ethics in banking sector as Kuching. Then, it will cover on definition the code of ethics in organization. Next, will elaboration the purpose code of ethics for employees’ in banking sector. Lastly, will explaining the effective code of ethics and wrap up on the conceptual framework for this research.